Doubling Pharmacist Coverage in the Intensive Care Unit: Impact on the Pharmacists' Clinical Activities and Team Members' Satisfaction. Issue 8 (September 2017) - McDaniel, Joshua; Bass, Lynn; Pate, Toni; DeValve, Michael; Miller, Susan
Background: National professional organizations have recognized pharmacists as essential members of the intensive care unit (ICU) team. Critical care pharmacists' clinical activities have been categorized as fundamental, desirable, and optimal, providing a structure for gauging ICU pharmacy services being provided.Objective: To determine the impact the addition of a second ICU pharmacist covering 30 adult ICU beds at a large regional medical center has on the complexity of pharmacists' interventions, the types of clinical activities performed by the pharmacists, and the ICU team members' satisfaction.Methods: A prospective mixed-method descriptive study was conducted. Pharmacists recorded their interventions and clinical activities performed. A focus group composed of randomly selected ICU team members was held to qualitatively describe the impact of the additional pharmacist coverage on patient care, team dynamics, and pharmacy services provided.Results: The baseline period consisted of 33 days, and the intervention period consisted of 20 days. The average complexity of interventions was 1.72 during the baseline period (mode = 2) versus 1.69 (mode = 2) during the intervention period. The number of desirable and optimal clinical activities performed daily increased during the intervention from 8.4 (n = 279) to 16.4 (n = 328) and 2.3 (n = 75) to 8.6 (n = 171) compared with the baseline, respectively. Focus group members qualitatively described additional pharmacist coverage as beneficial.Conclusion: The additional critical care pharmacist did not increase pharmacy intervention complexity; however, more interventions were performed per day. Additional pharmacist coverage increased the daily number of desirable and optimal clinical activities performed and positively impacted ICU team members' satisfaction.